2022
DOI: 10.3390/foods11213521
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Bacterial Foodborne Pathogens Isolated from Raw Bivalve Molluscs Subjected to Consumption in Poland during a Ten-Year Period

Abstract: The aim of this study was to evaluate the microbiological contamination of raw bivalve molluscan shellfish (BMS) available on the Polish market and determinate the antimicrobial resistance of the obtained isolates. A total of 1000 mollusc samples were tested for the presence of Salmonella spp., L. monocytogenes, V. parahaemolyticus, and S. aureus using the ISO standard methods. Additionally, the bacterial isolates’ susceptibility to antimicrobials was determined using the minimum inhibitory concentration (MIC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…All V. parahaemolyticus isolates had the toxR genes reported by some researchers [47,49]. However, a lower percentage was reported by some reports [51,52]. Meanwhile, [53] said higher results.…”
Section: Discussionmentioning
confidence: 83%
“…All V. parahaemolyticus isolates had the toxR genes reported by some researchers [47,49]. However, a lower percentage was reported by some reports [51,52]. Meanwhile, [53] said higher results.…”
Section: Discussionmentioning
confidence: 83%
“…Such isolates were identified both in food and food-processing environments. Other studies also identified strains resistant to clindamycin in other countries, although the percentages of such isolates were rather low ( 7 , 21 ). However, there are also reports of high resistance rates of L. monocytogenes isolates to this antimicrobial ( 11 , 15 , 29 ).…”
Section: Discussionmentioning
confidence: 98%
“…domestic animals used in food production or produce [16]. Shellfish surveillance studies have provided insight into the prevalence of Salmonella in shellfish, along with the serovars commonly connected with contamination [15,[17][18][19]. However, little work has been focused on the lineages commonly associated with shellfish, their relevance to human illness or the potential routes of contamination.…”
Section: Introductionmentioning
confidence: 99%